Tree-Structure Canopy: A Case Study in Design and Fabrication of Complex Steel Structures using Digital Tools. (March 2013) - Agkathidis, Asterios; Brown, André
This paper describes and reflects on the design and manufacturing process of the Tree-Structure canopy for the WestendGate Tower in Frankfurt upon Main, completed early 2011. The project investigated fabrication and assembly principles of complex steel structures as well as the integration of contemporary computational design, engineering, optimization and simulation techniques in a collaborative design approach. This paper focuses on the notion of modular standardization as opposed to non standard customized components. It also engages with issues relating to digital production tools and their impact on construction cost, material performance and tolerances. In addition it examines the reconfiguration of liability during a planning and construction process, an aspect which can be strongly determined by fabrication companies rather than the architect or designer. This paper is written as a reflection on the complete building process when contemporary digital tools are used from design through to fabrication. It studies both the generation of the steel structure as well the ETFE cushion skin. It reports on a collaborative project, where the main author was responsible for the canopies design, parameterization, digitalization and fabrication, as well as for the dissemination of the outcomes and findings during the design and realization process. As such it represents an example of research through design in a contemporary and evolving field. The canopy received a design award by the Hellenic Architecture Association.